Advancing healthcare through digital innovation: A bibliometric perspective on Saudi Arabia’s vision 2030 - Bengana, Ismail; Brika, Said Khalfa; Mili, Khaled (Edelweiss Applied Science and Technology, 2025)
This study aims to perform a comprehensive bibliometric analysis of digital health research in Saudi Arabia from 1996 to 2024, identifying key contributors, evolutionary trends, and emerging themes to inform future initiatives aligned with Vision 2030. We analyzed 417 digital health-related documents from the Scopus database using VOSviewer and Biblioshiny tools to examine co-authorship patterns, citation clusters, and keyword associations. This quantitative approach allowed for systematic mapping of the digital health research landscape in Saudi Arabia. The analysis revealed influential authors, robust collaborative networks, and distinct thematic clusters in telemedicine, mHealth, electronic health records, and artificial intelligence applications. Highly cited publications demonstrated research concentration in oncology, aging populations, and diagnostic screening. Saudi Arabia’s expanding international collaborations, particularly with the UK and US, reflect its growing prominence in global digital health research. Saudi Arabia has made significant progress in digital health research, with increasing publication output and international collaboration networks that support its Vision 2030 healthcare objectives. The bibliometric data indicates an evolving research focus from basic infrastructure to advanced applications of AI and personalized medicine. This study provides valuable insights for policymakers, researchers, and healthcare administrators by offering a data-driven foundation for strategic planning, resource allocation, and institutional collaborations in digital health initiatives across the Kingdom.